The symbiotic role of the endowment system in achieving sustainable development - presentation of the Algerian experience in the investment of endowments- - لمزري مفيدة (Milev Journal of Research and Studies, 2019)
Endowment plays a significant role in development through many of the activities which he is financing(Education, health, social services, etc.) however, the narrow view of the endowment as a religious institution means the affairs of mosques and those who maintain them only, Led to the focus of studies on the religious dimension without regard to the economic dimension social and financial conditions of the endowment, in this paper I have attempted to highlight the effective role which is carried out by the endowment institutions in order to achieve the comprehensive development of the state, and the impact on the economy and society and the areas that contribute to finance, by addressing the Algerian experience in the investment of endowment property its stages and the legal framework it governs, as for the result obtained through research, the Algerian experience is still in its infancy and needs to benefit from the experiences of other countries